Adverse Childhood Experiences Lead to Depression - Heinrich, Macy; Jesseph, Brooklyn; Shields, Colette (Kansas State University. K-State Libraries., 2019)
This study focuses on Adverse Childhood Experiences (ACE) and the link between adulthood depression in the Hispanic culture. The two variables, ACE scores and depression, will be evaluated and examine how they correlate with one another. This study hypothesizes how the higher the ACE score an individual has, the more likely they are to experience depression as an adult. The target population will be hispanic individuals above the age of 25. The reason behind wanting to focus on the Hispanic culture is because past studies have mainly focused on predominantly white cultures and because individuals need to understand the full impact of their experiences and how better approaches can be created to help them address their potential trauma and mental illness. This study further investigates how impactful childhood experiences have on an individual’s adulthood and how it can be helpful for practitioners to better understand their clients in a way that can be beneficial for both client and practitioner. It is important to study all populations, not just the majority group, in the United States so that research will not be overgeneralized.
Kirmser Undergraduate Research Award - Group category, grand prize
Keywords: adverse childhood experiences; adult depression; adult mental illness; Hispanic culture